Genome-Wide Anaplasma phagocytophilum AnkA-DNA Interactions Are Enriched in Intergenic Regions and Gene Promoters and Correlate with Infection-Induced Differential Gene Expression - Dumler, J. Stephen; Sinclair, Sara H.; Pappas-Brown, Valeria; Shetty, Amol C. (Frontiers in Cellular and Infection Microbiology, 2016)
Anaplasma phagocytophilum, an obligate intracellular prokaryote, infects neutrophils, and alters cardinal functions via reprogrammed transcription. Large contiguous regions of neutrophil chromosomes are differentially expressed during infection. Secreted A. phagocytophilum effector AnkA transits into the neutrophil or granulocyte nucleus to complex with DNA in heterochromatin across all chromosomes. AnkA binds to gene promoters to dampen cis-transcription and also has features of matrix attachment region (MAR)-binding proteins that regulate three-dimensional chromatin architecture and coordinate transcriptional programs encoded in topologically-associated chromatin domains. We hypothesize that identification of additional AnkA binding sites will better delineate how A. phagocytophilum infection results in reprogramming of the neutrophil genome. Using AnkA-binding ChIP-seq, we showed that AnkA binds broadly throughout all chromosomes in a reproducible pattern, especially at: (i) intergenic regions predicted to be MARs; (ii) within predicted lamina-associated domains; and (iii) at promoters ≤ 3000 bp upstream of transcriptional start sites. These findings provide genome-wide support for AnkA as a regulator of cis-gene transcription. Moreover, the dominant mark of AnkA in distal intergenic regions known to be AT-enriched, coupled with frequent enrichment in the nuclear lamina, provides strong support for its role as a MAR-binding protein and genome “re-organizer.” AnkA must be considered a prime candidate to promote neutrophil reprogramming and subsequent functional changes that belie improved microbial fitness and pathogenicity.